SPECTROPHOTOMETRIC DETERMINATION OF ATORVASTATINE CALCIUM - O. Yu. Myronova; S. O. Vasjuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
Atorvastatin Calcium reduces the level of cholesterol and lipoproteins in blood plasma, inhibits cholesterol synthesis in liver, increasing the number of low-density lipoproteins. It also reduces cholesterol in patients with homozygous familial hypercholesterolemia, which is usually resistant to lipid-lowering therapy. In today's world physical and chemical methods of analysis,including absorption spectrophotometry in the visible spectrum, which is characterized by ease of performance, availability, accuracy and selectivity,playsleadership role in quality assurance of medicines,